Pulmonary hypertension and NT-proBNP dynamics during the course of adulticide treatment in dogs naturally infected by Dirofilaria immitis - Noelia Costa-Rodríguez; Daniel Julio Vera-Rodríguez; Soraya Falcón-Cordón; Beatriz Regina Morales; José Alberto Montoya-Alonso; Rodrigo Morchón; Elena Carretón (Parasites & Vectors)
Abstract Background Pulmonary hypertension (PH) is a frequent complication in dogs with heartworm disease caused by Dirofilaria immitis. Although echocardiography remains the main diagnostic tool, its operator- and preload-dependence may limit accuracy. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a cardiac biomarker that increases in response to ventricular wall stress and may be useful for monitoring right-sided heart disease. This study aimed to evaluate NT-proBNP concentrations in dogs with precapillary PH due to heartworm disease during adulticide treatment. Methods In total, 90 dogs diagnosed with heartworm disease were prospectively enrolled and classified according to the presence of PH based on echocardiographic criteria. NT-proBNP concentrations were measured on days 0, 30, 60, and 90 of adulticide treatment. Additional data collected included the presence/absence of microfilariae, clinical signs, parasite burden, and renal values. Dogs received adulticidal therapy following current international guidelines. Statistical analyses assessed correlations between NT-proBNP levels, epidemiological, clinical and echocardiographic classification, and treatment progression. Results Dogs with PH had significantly higher NT-proBNP concentrations at baseline compared with those without PH (2038 ± 1671 versus 583 ± 185 pmol/L, P < 0.001). NT-proBNP levels were also positively correlated with parasite burden (r = 0.530, P < 0.05), presence of clinical signs (r = 0.456, P < 0.05), and age (r = 0.29, P < 0.05). During treatment, a progressive decrease in NT-proBNP concentrations was observed in dogs with PH, while levels remained stable in dogs without PH. Receiver operating characteristic (ROC) analysis identified a cut-off of 1524.8 pmol/L for detecting moderate-to-severe PH (sensitivity: 99%, specificity: 87%). Conclusions NT-proBNP is a valuable noninvasive biomarker for detecting and monitoring PH in dogs with heartworm disease. Its concentrations seem to reflect parasite burden, clinical status, and echocardiographic severity, and decline progressively with adulticide therapy. Integration of NT-proBNP into diagnostic and therapeutic protocols may enhance management of heartworm-infected dogs with suspected PH. Graphical Abstract